1999
DOI: 10.1103/physreve.59.4687
|View full text |Cite
|
Sign up to set email alerts
|

Master-slave scheme and controlling chaos in the Braiman-Goldhirsch method

Abstract: This Brief Report presents a master-slave scheme to demonstrate explicitly how control chaos works in the Braiman-Goldhirsch method for the one-dimensional map system. The scheme also naturally explains why the anomalous responses arise in a periodically perturbed, unimodal map system. The extension of the masterslave scheme to the D-dimensional map is also presented. ͓S1063-651X͑99͒03404-2͔

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In the nonfeedback control systems, on the other hand, the applied perturbation is independent of the state of the system. So far, controlling chaos by applying a suitable weak periodic perturbation, which is sometimes called taming chaos, 3) has been studied in a variety of chaotic dynamical systems both theoretically [4][5][6][7] and experimentally. 8) Recently, analyzing a constrained system in which a one-dimensional Poincaré map is derived, Tamura et al 4) showed that taming chaos occurs by a saddle node bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…In the nonfeedback control systems, on the other hand, the applied perturbation is independent of the state of the system. So far, controlling chaos by applying a suitable weak periodic perturbation, which is sometimes called taming chaos, 3) has been studied in a variety of chaotic dynamical systems both theoretically [4][5][6][7] and experimentally. 8) Recently, analyzing a constrained system in which a one-dimensional Poincaré map is derived, Tamura et al 4) showed that taming chaos occurs by a saddle node bifurcation.…”
Section: Introductionmentioning
confidence: 99%